The openCARP simulation environment for cardiac electrophysiology. (September 2021) - Plank, Gernot; Loewe, Axel; Neic, Aurel; Augustin, Christoph; Huang, Yung-Lin; Gsell, Matthias A.F.; Karabelas, Elias; Nothstein, Mark; Prassl, Anton J.; Sánchez, Jorge; Seemann, Gunnar; Vigmond, Edward J.
Highlights: We present the openCARP simulation environment as a solution that could foster the needs of large parts of the computational cardiac electrophysiology community. Together with the Python-based carputils framework, openCARP allows developing and sharing simulation pipelines to increase reproducibility and productivity. openCARP focuses on usability and performance for cardiac electrophysiology simulations. We provide extensive training material and a community platform as a basis for a vivid user community. Abstract: Background and Objective: Cardiac electrophysiology is a medical specialty with a long and rich tradition of computational modeling. Nevertheless, no community standard for cardiac electrophysiology simulation software has evolved yet. Here, we present the openCARP simulation environment as one solution that could foster the needs of large parts of this community. Methods and Results: openCARP and the Python-based carputils framework allow developing and sharing simulation pipelines which automate in silico experiments including all modeling and simulation steps to increase reproducibility and productivity. The continuously expanding openCARP user community is supported by tailored infrastructure. Documentation and training material facilitate access to this complementary research tool for new users. After a brief historic review, this paper summarizes requirements for a high-usability electrophysiology simulator and describes how openCARP fulfills them. We introduce the openCARP modeling workflow in a multi-scale example of atrial fibrillation simulations on single cell, tissue, organ and body level and finally outline future development potential. Conclusion: As an open simulator, openCARP can advance the computational cardiac electrophysiology field by making state-of-the-art simulations accessible. In combination with the carputils framework, it offers a tailored software solution for the scientific community and contributes towards increasing use, transparency, standardization and reproducibility of in silico experiments.